Synergy Between Low Dose Metronomic Chemotherapy and the pH-Centered Approach Against Cancer - Koltai, Tomas (Int J Mol Sci, 2019)
Low dose metronomic chemotherapy (MC) is becoming a mainstream treatment for cancer in veterinary medicine. Its mechanism of action is anti-angiogenesis by lowering vascular endothelial growth factor (VEGF) and increasing trombospondin-1 (TSP1). It has also been adopted as a compassionate treatment in very advanced human cancer. However, one of the main limitations of this therapy is its short-term effectiveness: 6 to 12 months, after which resistance develops. pH-centered cancer treatment (pHT) has been proposed as a complementary therapy in cancer, but it has not been adopted or tested as a mainstream protocol, in spite of existing evidence of its advantages and benefits. Many of the factors directly or indirectly involved in MC and anti-angiogenic treatment resistance are appropriately antagonized by pHT. This led to the testing of an association between these two treatments. Preliminary evidence indicates that the association of MC and pHT has the ability to reduce anti-angiogenic treatment limitations and develop synergistic anti-cancer effects. This review will describe each of these treatments and will analyze the fundamentals of their synergy.